Assessing the Critical Post-COVID Mental-Health Concerns amongst Students, Parents and Teaching/Non-Teaching Staff: An Investigation into the Effectiveness of Coping Strategies - Ashraya Kant; Anjali Singh (International Journal For Multidisciplinary Research, 2026)
Considering the difficulties and challenges in social psychological research pertaining to the validity and credibility of the assertions made therein, this study tended towards methodological robustness through outrightly explicating the limitations through which it is acquiring information. This study investigated the concerns pertaining to mental health in the aftermath of COVID, interrogating how the global pandemic was an implicit disruption in the conventional functioning of educational institutions and how it stemmed doubts and grief regarding the learning potential, although, it was coupled with the rise of technological advancements but the “know-how” and the creation of the right mental and physical space that enable education are premised on a sense of embeddedness and embodiment which were disrupted during the global pandemic, this paper investigates the mental health concerns that have gained prominence in the backdrop of Covid epidemic amongst various stakeholders involved in school level pedagogical practices (i.e., students, parents and teaching/non teaching staff). This study relies on global and national level secondary data, as well as, conducts primary data collection amongst 95 respondents in different cohorts (50 students, 20 parents, and 15 teaching and 10 non-teaching staff). This study not only tends to identify and map the mental health concerns that were gaining prominence, but rather how the respondents were attempting to address and cope with them.